An integrated approach for TQM implementation in SMEs - Pereira, Zulema L. (2008)
This paper tackles the broad issue of TQM implementation in SMEs. It includes a review of two models aimed at improving organisational performance, the EFQM Excellence Model and the Balanced Scorecard, which have been widely used in large organisations. Both models are examined as to their suitability and applicability to small and medium sized enterprises. The findings indicate that SMEs can benefit from the adoption of an integrated approach that combines both models if some critical factors are considered in the implementation process. A theoretical framework is proposed, which considers such integration and leads to a gradual implementation of TQM principles and methods in SMEs.